Analysis of sales volumes of herbal remedies with hemostatic effect - U. V. Karpiuk; I. S. Cholak; O. I. Yemelianova; V. S. Kyslychenko (Zaporozhye State Medical University, 2019)
The aim of the study. Determination of sales volumes of drugs with hemostatic action and analysis of sales features of plant hemostatic drugs. Materials and methods. The market research and sales volumes of hemostatic drugs were carried out using the content analysis of the State Register of medicines and according to the analytical system of research of the pharmaceutical market Pharm-Xplorer/Pharm standard of Proxima Research Company. Results. The assortment of registered hemostatic drugs on the Ukrainian market and the availability of these drugs according to sales data in the retail segment were analyzed. The presence of hemostatic drugs of the plant origin in the market of foreign countries has been analyzed. The dynamics of sales of hemostatic medicines and in particular of herbal drugs in natural and monetary equivalents in the pharmaceutical market of Ukraine was researched. The segments of medicine in which hemostatic drugs are prescribed were analyzed. The volume of sales of herbal means of hemostatic action compared with other hemostatic drugs in some medical segments was investigated. Conclusions. Available 76.5 % of medicine are from the assortment of registered hemostatic drugs. There are no preparations of plant origin with hemostatic action of foreign manufacturers in the Ukrainian market. The leader in sales in monetary terms is tranexamic acid - 33%. Hemostatic agents of plant origin are in a small and low-grade group of drugs. Antihemorrhagic agents of plant origin are most often prescribed in gynecology and are most commonly sold through non-prescription pharmacy sales.